The Routledge companion to theatre and performance historiography
1 online resource (xxi, 495 pages)
Keywords: "The Routledge Companion to Theatre and Performance Historiography sets the agenda for inclusive and wide-ranging approaches to writing history, embracing the diverse perspectives of the twenty-first century and Critical Media History. Written by an international team of authors whose expertise spans a multitude of historical periods and cultures, this collection of fascinating essays poses the central question: 'what is specific to the historiography of the performative?' The study of theatre, in conjunction with the wider sphere of performance, involves an array of multi-faceted methods for collecting evidence, interpreting sources and creating meaning. Reflecting on issues of recording - from early modern musical scores, through VHS-technology to latest digital procedures - and on what is missing from records or oblique in practices, the contributors convey how theatre and performance history is integral to social and cultural relations. This expertly curated collection repositions theatre and performance history and is essential reading for Theatre and Performance Studies students or those interested in social and cultural history more generally"--